Penggunaan Eufemisme dalam Penulisan Judul Berita Pada “Rubrik Hukum” Surat Kabar Daring Radar banten.co.id Periode September s.d. November 2022 - Ike Mutia (Journal on Education, 2022)
This research is motivated by the use of euphemisms used by journalists in writing news headlines. Euphemisms are subtle expressions that have a positive connotation so as not to offend other people. The purpose of this study is to describe the use of euphemisms, euphemism references, and euphemism functions in writing news titles for the legal rubric of the online newspaper radarbanten.co.id for the period septembers.d. november 2022. The data in this study are in the form of words, phrases, and clauses with the data source being the online newspaper radarbanten.co.id for the period September to. november 2022. The data collection technique used in this research is the observing technique and the note-taking technique. The results of the research that have been analyzed show that the use of euphemisms is used in writing news titles in the legal rubric of the online newspaper radarbanten.co.id from September to September. november amounted to 10 data. The form of euphemism found in writing news titles in the legal section of the online newspaper radarbanten.co.id from September to September. november 2022 in the form of basic words totaling 3 data, derived words totaling 4 data, compound words totaling 1 data, and verb phrases totaling 1 data. Based on the forms of euphemisms that have been studied, there are 2 data for euphemism references referring to activities, 5 data for euphemism references referring to events, and 3 data for euphemism references referring to characteristics or circumstances. The euphemism function used in the context of writing news titles in the legal rubric of the online newspaper radarbanten.co.id from September to September. november 2022 as a tool for smoothing speech.